New Evidence of the Monophyletic Relationship of the Genus Psammolestes Bergroth, 1911 (Hemiptera, Reduviidae, Triatominae) - Oliveira, Jader [UNESP]; Chaboli Alevi, Kaio Cesar [UNESP]; Ravazi, Amanda [UNESP]; Herrera, Heitor Miraglia; Santos, Filipe Martins; Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP]; Rosa, Joao Aristeu da [UNESP] (Amer Soc Trop Med & Hygiene, 2018)
The genus Psammolestes within the subfamily Triatominae and tribe Rhodniini comprises the species Psammolestes arthuri, Psammolestes coreodes, and Psammolestes tertius, all potential vectors of Chagas disease. A feature of Psammolestes is their close association with birds, which makes them an interesting model for evolutionary studies. We analyzed cytogenetically Psammolestes spp., with the aim of contributing to the genetic and evolutionary knowledge of these vectors. All species of the Psammolestes showed the same chromosomal characteristics: chromocenter formed only by sex chromosomes X and Y, karyotype 2n = 22 and constitutive heterochromatin, and AT base pairs restricted to the sex chromosome Y. These results corroborate the monophyly of the genus and lead to the hypothesis that during the derivation of P. tertius, P. coreodes, and P. arthuri from their common ancestor, there was no reorganization in the number or structure of chromosomes.